2012
DOI: 10.3354/meps09542
|View full text |Cite
|
Sign up to set email alerts
|

El Niño induced changes to the Bolivar Channel ecosystem (Galapagos): comparing model simulations with historical biomass time series

Abstract: During a strong El Niño event, nutrient and phytoplankton concentrations around the Galapagos archipelago greatly decrease, while sea surface temperature increases (> 7°C). Several species suffer under these conditions, while some benefit and new species appear. To understand the mechanisms behind observed changes, a trophic reference model of the Bolivar Channel ecosystem was forced by a 16 yr (1994 to 2009) satellite-derived time series of phytoplankton biomass including the El Niño period 1997/98. Emergent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 30 publications
0
34
0
2
Order By: Relevance
“…Thus, heavily grazed reefs with crustose coralline algae, "urchin barrens," replaced former macroalgal and coral habitats, resulting in declines in biodiversity (Edgar et al 2010). Wolff et al (2012a) evaluated the dynamics of subtidal communities and marine vertebrates during the period 1994-2009, based on a trophic mass balance model of the Bolivar Channel ecosystem, the most productive area of the archipelago. These authors showed that SST increased by 7°C during the 1997/1998 El Niño, when phytoplankton concentration decreased by 46% and 33%, respectively, and the ecosystem size (total energy throughput) was reduced by 70%.…”
Section: Negative and Positive Effects Of El Niño: Galápagos As A Casmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, heavily grazed reefs with crustose coralline algae, "urchin barrens," replaced former macroalgal and coral habitats, resulting in declines in biodiversity (Edgar et al 2010). Wolff et al (2012a) evaluated the dynamics of subtidal communities and marine vertebrates during the period 1994-2009, based on a trophic mass balance model of the Bolivar Channel ecosystem, the most productive area of the archipelago. These authors showed that SST increased by 7°C during the 1997/1998 El Niño, when phytoplankton concentration decreased by 46% and 33%, respectively, and the ecosystem size (total energy throughput) was reduced by 70%.…”
Section: Negative and Positive Effects Of El Niño: Galápagos As A Casmentioning
confidence: 99%
“…This was reflected in the reduction of pelagic and demersal fish, seabirds, reptiles, and marine mammals. Wolff et al (2012a) suggested that bottomup effects largely control the system during El Niño events.…”
Section: Negative and Positive Effects Of El Niño: Galápagos As A Casmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface ocean temperature is the most analyzed oceanographic variable regarding the "El Niño" phase and its ecosystem effects in oceanic and coastal marine zones [13]. Nevertheless, estuarine zones are expected to experience a greater impact of hydrologic effects (fresh water or ocean water inputs) [14].…”
Section: Introductionmentioning
confidence: 99%